Morphological and molecular characters of Lemuru fish (Sardinella lemuru) from Tanjung Luar Waters, East Lombok - Abdul Syukur; Lalu Zulkifli; H. Mahrus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Lemuru fish from the Clupeidae family in various countries have many similarities that are difficult to distinguish between one species and another. This study aims to determine the morphological and molecular characteristics, genetic diversity, and kinship of lemuru fish in Tanjung Luar waters with lemuru fish species in countries. The molecular feature of lemuru fish used in this study was a marker for the cytochrome c oxidase subunit 1 (CO1) gene. The lemuru fish sample used in this study was lemuru caught in the waters of Tanjung Luar by small-scale fishermen. Lemuru fish sampling method using random, totaling 100 individuals. Firstly, the lemuru fish samples were grouped based on morphological characters. Next, segregation and augmentation of the CO1 gene DNA in five lemuru fish samples using a pair of primers. The amplification of DNA about 700 bp in size was sequenced. CO1 gene sequence data of lemuru samples were analyzed using MEGA 11 Software (Molecular Evolutionary Genetics Analysis) Version 11. The phylogenetic relationships obtained showed that the lemuru samples from Tanjung Luar waters, East Lombok, is in the same clade as Sardinella Jussieu from Malaysia and has a very close kinship relationship.